The Butlers in England and Ireland, 1405-1515 - Beresford, David (Trinity College (Dublin, Ireland). Department of History, 1999)
This thesis is a study of the Butler family in England and Ireland in the fifteenth century and, as such, has two main aims. The first of these is to provide a coherent picture of the history of the Butler family over the period 1405 to 1515. To do this, it will consider the place of the Butlers within the lordship of Ireland, the role of the earls of Ormond within their family and the effects of the prolonged absence of the earls of Ormond from their lordship in Ireland. The work moves between England and Ireland assessing the actions and the activities of the earls of Ormond in England and their kinsmen in Ireland. Foremost among these actions was the continual support given by the earls to the Lancastrian dynasty and the price they paid for supporting Henry VI and their attempts to regain their position in England during the reign of Henry VII. A second aim of this thesis is to use the experiences of the Butler family to provide material for the study of Anglo-Irish society in the later Middle Ages. Among the topics considered are the extent of the process of Gaelicisation, the bonds that held a great Anglo-Irish lineage together and the effects of long term absenteeism on those bonds.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin